The Level of Knowledge of Early Childhood Department Student on Psychological Support Methods for Post-Traumatic Stress Disorder in Children - Alqout, Hajar Abdullah; Alsedrani, Gadah Saleh (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the knowledge of female students in the Early Childhood Education Department regarding psychological support strategies for children with post-traumatic stress disorder (PTSD). Specifically, it investigated their awareness of PTSD symptoms in children and the steps required to manage such cases. The researchers employed a descriptive-analytical method to collect data and address the research questions. A comprehensive survey was conducted, targeting all seventh- and eighth-level students enrolled in the first semester of the academic year 1446/2024, with a total sample of 51 students. To achieve the research objectives, the researchers designed a questionnaire consisting of 27 items measuring students’ knowledge of PTSD symptoms and coping strategies. The findings revealed that the overall knowledge of early childhood education students about psychological support methods for children with PTSD was generally low. While awareness of symptoms was moderate, knowledge of coping strategies was weak. Responses largely centered on observing behaviors during play and using exploratory questions, with higher recognition given to techniques such as “relaxation” and “creating a safe environment.” However, the results also highlighted significant gaps in understanding professional aspects such as collaboration with families and defining the teacher’s role. These findings underscore the need to strengthen academic training to improve both psychological and pedagogical competencies. In light of the results, the study recommends developing educational programs, enhancing practical training, raising awareness of PTSD and its manifestations, teaching children coping skills for difficult emotions, distinguishing between problematic and exhausting behaviors, designing integrated psycho-educational-social programs, and enriching knowledge about building strong family partnerships and engaging parents.